Evaluating the Innovation Activities of Vietnamese Enterprises: Evidence from Binh Dinh Province - Thi Le Hang Nguyen; Ngoc Tien Nguyen; Dinh Manh Dam; Quyet Thang Dao; Thi Thanh Binh Le (My University, 2020)
Evaluating the Innovation Activities of Vietnamese Enterprises: Evidence from Binh Dinh Province
Keywords: Innovation Activities; Evaluation; Binh Dinh